O cinema como instrumento de sensibilização ambiental para conservação da água - Maria, Flávia Regina (Universidade Federal de São Carlos, 2017)
Cinema can be used for many purposes nowadays, such as: entertaining, educating and also as an important device able of spreading knowledge, provoking reflections on relevant themes, such as the water issue, its scarcity and the need for its conservation and preservation. In this context, the objective of the research was to analyze the influence of environmental cinema as a means of environmental perception and its sensitizing impact on individuals for water conservation. The exploratory research presents results obtained by primary data, involving the selection of volunteers; a pre-selection of films addressing the water theme to compose a list; the selection of four films from this list for the consideration of the participants; the characterization, description, interpretation and brief analysis of the films selected for the research; and the application of questionnaires, being a preliminary on perception with respect to water, and a conclusive about the sensitizing impact of the films. The secondary data of the research were obtained by means of a bibliographical survey and reading of the material on the theme water; environmental film; cinema and water; conservation and preservation of water; and environmental perception and awareness. The results obtained were positive for the use of cinema as a sensitizing instrument, awakening in the participants a greater reflection on the uses of water and its importance for the maintenance of life.
The cinema as an instrument of environmental awareness for water conservation
Keywords: Percepção e sensibilização ambiental; Cinema ambiental; Conservação da água; Environmental perception and awareness; Environmental cinema; Conservation of water; OUTROS::CIENCIAS